Need for criteria and indicators for SFM as a means of monitoring the compliance of the national forest policy in India - Prabhu, Ravi (Indian Institute of Forest Management, 2001)
The paper examines the implications of using criteria and indicators for sustainable management as tools for policy feedback in the context of India's forests. It explores some of the theoretical underpinnings of developing and implementing policy in the face of complexity and establishes a role for criteria and indicators as negotiated and scientifically sound tools for for providing feedback on the effectiveness of policy. Examples of criteria and indicator development across the globe are explored with respect to their information for India's needs. Finally the paper examines how criteria and indicators of the Bhopal-India process might be applied.